2019
DOI: 10.1101/756833
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutation of theALBOSTRIANSOhnologous GeneHvCMF3Impairs Chloroplast Development and Thylakoid Architecture in Barley due to Reduced Plastid Translation

Abstract: Gene pairs resulting from whole genome duplication (WGD), so-called ohnologous genes, are retained only if at least one gene of the pair undergoes neo- or subfunctionalization. Sequence-based phylogenetic analyses of the ohnologous genes ALBOSTRIANS (HvAST/HvCMF7) and ALBOSTRIANS-LIKE (HvASL/HvCMF3) of barley (Hordeum vulgare) revealed that they belong to a newly identified subfamily of genes encoding CCT domain proteins with putative N-terminal chloroplast transit peptides. Recently, we showed that HvCMF7 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(33 citation statements)
references
References 84 publications
4
29
0
Order By: Relevance
“…The more serious effect of the two mutations in cia2cil compared to cia2 on 16S and 23SrRNA processing, chlorophyll content, thylakoid/grana structure and, in particular, photosynthetic parameters may be responsible for the slower growth of cia2cil vs. cia2, cil and wild type. Mutant analyses demonstrated that inefficient chloroplast translation is often associated with altered organization of the thylakoid membrane system (Fristedt et al, 2014;Liu et al, 2015;Zhang et al, 2017;Li et al, 2019a). The delayed greening phenotype of cia2cil resembles the rbf1-1 mutant with defects in chloroplast translation due to inefficient processing of 16S rRNA (Fristedt et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The more serious effect of the two mutations in cia2cil compared to cia2 on 16S and 23SrRNA processing, chlorophyll content, thylakoid/grana structure and, in particular, photosynthetic parameters may be responsible for the slower growth of cia2cil vs. cia2, cil and wild type. Mutant analyses demonstrated that inefficient chloroplast translation is often associated with altered organization of the thylakoid membrane system (Fristedt et al, 2014;Liu et al, 2015;Zhang et al, 2017;Li et al, 2019a). The delayed greening phenotype of cia2cil resembles the rbf1-1 mutant with defects in chloroplast translation due to inefficient processing of 16S rRNA (Fristedt et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…After antibiotic screening with hygromycin, 24 plants were selected from each of the Col-0, cia2 mutant and HvCMF3 families, and 96 plants were selected from each of the HvCMF7 and ▲cTP_CIA2 families. The selected plants were transferred into the imaging system and phenotyping was performed following the protocols described previously (Li et al, 2019a) with the following modifications. For experiment I, measurement of PSII operating efficiency (ΦPSII) and electron transport rate (ETR) were performed for light adapted plants.…”
Section: High-throughput Automated Imaging-based Phenotypingmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary leaves were collected from 7-day-old seedlings of wild type and variegated mutant (luteostrians-P1). Preparation of 1-2 mm 2 leaf cuttings for ultrastructure analysis including aldehyde/osmium tetroxide fixation, dehydration, resin infiltration and ultramicrotomy were performed as previously described (Li et al, 2019a).…”
Section: Ultrastructural Analysismentioning
confidence: 99%